Modified basic and specific (BASP) classification for pattern hair loss. (23rd June 2019) - Kim, Beom Jun; Choi, Jaewoong; Choe, Sung Jay; Lee, Solam; Lee, Won‐Soo
Abstract: Background: In 2007, Lee et al . introduced a basic and specific (BASP) classification for pattern hair loss that was comprehensive and applicable regardless of race or gender. However, this BASP classification has several limitations. Frontal type hair loss classification is relatively crude, and a specific hair loss pattern cannot be ascertained when hair loss is associated with the temporal and occipital areas. Methods: In our modified BASP classification, frontal type classification was subdivided into five instead of three grades. Basic type classification remained the same as in the previous method. In addition, information regarding the involvement of the temporal or occipital scalp was recorded. Accuracy and ease of use were evaluated and compared with the existing BASP classification in 138 patients with pattern hair loss. Results: Temporal or occipital involvement was observed in 14 patients, accounting for 11.1% of subjects. Final type accuracy was 82.5% in the existing BASP classification and 71.4% in the modified classification. Ease of use for two practitioners was 70.2 and 72.1% for the existing BASP classification, and 48.9 and 52.2% for the modified method. Conclusion: We expect that the modified BASP classification will overcome the limitations of the existing BASP classification. We believe this modified classification will be a valuable tool for pattern hair loss classification because of its classification of previously unclassified types.